Leaching of rare earth elements from bastnasite ore (second part) - Stopić, Srećko R.; Friedrich, Bernd G. (Vojnotehnički glasnik / Military Technical Courier, 2019)
Dissolution of rare earth elements from bastnasite ore was studied using different leaching agents such as sulfuric acid, hydrochloric acid, acetic acid, citric acid and sodium hydroxide at 70°C, with 1mol/L, s/L ratio of 0.05 between 30 and 180 min. The one-step direct leaching strategy was applied under atmospheric pressure aiming at selective leaching of rare earth elements from a matrix of iron oxides in which the rare earth elements – carbonates & flourides – are embedded.
Keywords: rare earth elements; hydrometallurgy; bastnasite; acids